Analysis of the Judge's Consideration on the Decision of the Central Jakarta District Court Number 157/Pid.B/2024/PN Jkt.Pst In The Case Of Online Concert Ticket Fraud - Malika Baby Natasha; R. Rahaditya (Journal of Law, Politic and Humanities, 2025)
This study seeks to examine the judicial interpretation underlying the judge's rationale in Central Jakarta District Court Decision Number 157/Pid.B/2024/PN Jkt.Pst, concerning the case of online concert ticket fraud involving defendant Ghisca Debora Aritonang. The main focus of this research is to understand how the judge handed down the verdict and how the verdict interprets the legal provisions regarding fraud in digital transactions. Using a normative legal research method with a statutory approach, the results of the analysis show that the judge's consideration in this decision is very in-depth and comprehensive. The results showed that the judge considered various legal aspects and facts revealed during the trial, ranging from the elements of fraud in accordance with Article 378 of the Criminal Code to malicious intent proven from evidence and witness testimony. In addition, the defendant's mental state and the social impact of the fraudulent act that harmed many people became the focus of the judge's attention. By emphasizing the absence of justification for the defendant's actions, the judge gave a firm decision that is expected to have a deterrent effect on other criminals. The legal interpretation in this decision reflects the application of the principles of justice and accountability in criminal law in Indonesia. It is hoped that there will be increased public education and awareness regarding the risks of online transactions as well as cooperation between law enforcement and concert organizers to facilitate safer transactions